Evaluation of regression of diabetes-induced nephropathy and vascular dysfunction in rats by Montelukast via antioxidative and anti-inflammatory actions - Hanan S. Anbar,, George S. G. Shehatou,, Mona Abdel-Rahim, Ghada M. Suddek, Nariman M. Gameil (Journal of Applied Pharmaceutical Science, 2023)
This research investigated the effects of montelukast (MONT), a leukotriene receptor antagonist, on diabetes-associated nephropathy and vascular dysfunction in streptozotocin (STZ) diabetic rats. STZ-diabetic Sprague-Dawley rats (a single STZ injection, 50 mg/kg, i.p.) were randomly allocated into three groups (n = 8 each): STZ (received the drug vehicle), STZ-LOS (received Losartan (LOS), 25 mg/kg/day, orally), and STZ-MONT (received MONT, 10 mg/kg/day, orally). Drug administration started 2 weeks after the induction of diabetes and continued till the end of the experiments (10 weeks). A group of age-matched normal rats was set as a control. After 70 days, urine and serum specimens were obtained for biochemical assessments. Moreover, in renal and/or aortic tissue homogenates, levels of reduced glutathione, superoxide dismutase, malondialdehyde, nitric oxide, tumor necrosis factorα (TNF-α), and transforming growth factor-β1 (TGF-β1) were assessed. Pathological alterations in diabetic kidneys and aorta were examined and the vascular reactivity of isolated aortic rings was investigated. MONT attenuated body weight loss, reduced diabetic renal hypertrophy, ameliorated glycated haemoglobin levels, improved renal functions, and lessened renal and aortic oxidative stress in STZ rats. Moreover, MONT reduced kidney levels of TNF-α and TGF-β1 compared to the untreated STZ group. MONT reduced histopathological alterations in renal tissues and diminished aortic medial thickness in diabetic animals. MONT also attenuated enhanced contractile reactivity of STZ aortas to phenylephrine. The effects of MONT were comparable to or surpassed those brought about by LOS treatment. In conclusion, MONT could offer comparable renoprotective and vasculoprotective effects to LOS in type 1 diabetic rats.
Keywords: Diabetes, nephropathy, Montelukast, oxidative stress, TNF-α, TGF-β1, vascular dysf